Nutritional knowledge and nutritional status of the recreationally active population - Pawlas, Agnieszka; Bielaszka, Agnieszka; Staśkiewicz, Wiktoria; Stelmach, Anna-Maria; Kiciak, Agata; Marek Kardas, Marek Kardas (Journal of Education, Health and Sport, 2022)
Introduction. Adequate nutrition combined with physical activity is the foundation of a healthy lifestyle. Recreational sportspersons should know how to adjust their nutrition to physical activity in order to benefit their health. The aim of the study was to assess the nutritional knowledge of recreationally active people and to assess the influence of BMI and gender on the level of nutritional knowledge. Material and methods. The study was conducted with the use of 200 participants aged 15-55 years living in the city of Katowice. The respondents were physically active at least 3 times a week for at least 1 hour. Nutritional knowledge was assessed through a self-administered questionnaire. Nutritional status was assessed by means of the BMI index, and for its assessment, the ranges recommended by the World Health Organization were adopted. Results. Most of the respondents - 33.5% (n=77) declared that they practiced weight training, 15.5% (n=31) attended group fitness classes, 14.5% (n=29) practiced running, fewer people practiced team sports and cycling. The nutrition knowledge of the majority of the respondents was at a sufficient level (n=136), 44 respondents had good nutrition knowledge and 22 respondents had insufficient nutrition knowledge. None of the respondents had very good nutrition knowledge. More than 70% of respondents had normal BMI (n=142), more than 25% (n=51) were overweight, and 7 subjects had BMI values below normal. Conclusions. There was no relationship between gender, BMI, and level of nutritional knowledge. The study shows that there is a need for nutritional education for recreational sportsmen.